2002
DOI: 10.2116/analsci.18.1301
|View full text |Cite
|
Sign up to set email alerts
|

Electron-capturing Derivatization of Neutral Steroids for Increasing Sensitivity in Liquid Chromatography/Negative Atmospheric Pressure Chemical Ionization-Mass Spectrometry

Abstract: Derivatization of neutral steroids for increasing sensitivity in liquid chromatography/negative atmospheric pressure chemical ionization-mass spectrometry (APCI-MS) has been examined. Under APCI conditions, gas-phase electrons are provided by the corona discharge and captured by electron-affinitive compounds. In negative APCI-MS, therefore, ultrahigh sensitivity can be obtained by tagging neutral steroids, whose ionization efficiencies are low in the conventional APCI-MS, with electron-capturing moieties, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…In positive MS/APCI, the introduction of proton-affinitive atoms, such as oxygen and nitrogen, to the analyte is very effective in increasing the sensitivity of the resulting derivative. 22) In the present study, 6-MITC and NAC were analyzed by directflow injection to optimize the MS conditions, and thereafter, they were analyzed by HPLC-MS. First, HPLC-MS/ESI was conducted but the results were not preferable. Therefore, HPLC-MS/APCI was conducted as an alternative method.…”
Section: Resultsmentioning
confidence: 99%
“…In positive MS/APCI, the introduction of proton-affinitive atoms, such as oxygen and nitrogen, to the analyte is very effective in increasing the sensitivity of the resulting derivative. 22) In the present study, 6-MITC and NAC were analyzed by directflow injection to optimize the MS conditions, and thereafter, they were analyzed by HPLC-MS. First, HPLC-MS/ESI was conducted but the results were not preferable. Therefore, HPLC-MS/APCI was conducted as an alternative method.…”
Section: Resultsmentioning
confidence: 99%
“…To improve ion formation in the ESI mode analytes have to be derivatized i.e., with electrophoric labels like pentafluorobenzyl chloride which generally requires sample work up comparable to the GC-MS procedure. Another possibility is the use of sources which allow the ionization of more lipophilic compounds like the atmospheric pressure chemical ionization (APCI) source [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Many derivatization reagents, such as N,N-dimethylaminonaphtalenesulfonyl (Dansyl) chloride, 25,26 p-nitrobenzoyl chloride, 27,28 pentafluorobenzyl bromide, 29,30 and 2-fluoro-Nmethylpyridinium-p-toluenesulfonate 31,32 for hydroxyl groups of steroid and lipid, and Girard-P, 33,34 O-ethylhydroxylamine hydrochloride, 35 2-hydrizino-N-methylpyridine, 36,37 and 2-nitro-4-trifluoromethylhydrazine 38,39 for steroidal carbonyl groups are reported. Ding et al, 40 Ali et al, 41 and Elba et al 42 recently reported that derivatization with silylating agents, such as BSTFA with 1% trimethylchlorosilane (TMCS), significantly increased sensitivity and selectivity by GC-MS detection of phenolic compounds, including estrogenic chemicals.…”
Section: Introductionmentioning
confidence: 99%